The Urgent as a Sociocultural Phenomenon of the Construction of the Present - Soghomonyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
Since New Ages in the foundation of the construction of social existence has laid a presumption according to which it is possible to provide the persistent progress whereby reason and rational organization of social system. The situation has changed in the postmodern world of institutionalized distrust. Because of the uncertainty of life situations the ignored social responsibilities are obeyed to personal success. Destroying the common system of norms and values the urgent as a way of construction of social reality becomes as a source of disorganization of postmodern society. As a result of the analysis the author comes to the conclusion that the construction of society of common welfare will not bring to the happiness of humanity if the search of this welfare will not be carried out of the context of spiritual needs. Therefore, the foundation of the construction of social existence should be not the coerced, depersonalized regularity, but the harmonic combination of different from outside, but, in effect, common moral values.